2017
DOI: 10.1177/1687814016686935
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on bladeless turbine using incompressible working medium

Abstract: The bladeless turbine has a promising future as a new power generation system. To explore the operating characteristics of the turbine, a bladeless turbine experimental platform with an incompressible working medium was designed and built. The relationships among performance parameters were analysed in experiments, and studies were conducted on the flow characteristics of the working medium inside the turbine using numerical simulation software. The causes of entry and exit losses were analysed. The data acqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…It means there is a specific rotational speed, which is the so-called "optimum speed", at which the TT generated power becomes the maximum. Li et al [38] also reported the same characteristic for the efficiency of a TT running with an incompressible carrier fluid in his experimental study. This optimum speed is not fixed but depends on the TT dimension (disk outer diameter), such that optimum speed decreases by increasing the disk diameter, and the magnitude of output power at the optimum point increases by decreasing the TT size.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…It means there is a specific rotational speed, which is the so-called "optimum speed", at which the TT generated power becomes the maximum. Li et al [38] also reported the same characteristic for the efficiency of a TT running with an incompressible carrier fluid in his experimental study. This optimum speed is not fixed but depends on the TT dimension (disk outer diameter), such that optimum speed decreases by increasing the disk diameter, and the magnitude of output power at the optimum point increases by decreasing the TT size.…”
Section: Resultssupporting
confidence: 53%
“…It implies that the TT emerged from computations on articles to the real world in around only one decade. Incompressible carrier fluid were employed to establish a performance relationship with other design parameters in experimental [38] and computational [33,39] studies. Additionally, a closed-form analytical solution was extracted for 2D analysis of incompressible fluid flow through rotating discs as a simplified form of TT configuration [40].…”
Section: Introductionmentioning
confidence: 99%
“…We performed uncertainty analysis based on the American Society of Heating, Refrigerating and Air Conditioning Engineers (ASHRAE) guidelines 22 and the literature. [23][24][25][26][27] The overall uncertainty of the convection coefficient (equation 5) was calculated based on the measured inlet water temperature (T i ), circular tube surface temperature (T s ), and water flow rate (Q); we derived error propagations (b h values) and random errors (p h values) (equation (6)). The combined standard uncertainty of propagation and random errors (multiplied by sensitivity factors) is given by equation (7).…”
Section: Uncertainty Analysismentioning
confidence: 99%
“…Nikola Tesla introduced this concept for radial bladeless turbines in 1913, driven only by the viscous forces of the flow impinging on the rotating disks [13]. Li et al [14] recently carried out experimental and numerical work for a Tesla turbine exposed to an incompressible fluid. Neckel and Godinho [15] designed convergent-divergent nozzles for Tesla turbines using air as working fluid.…”
Section: Introductionmentioning
confidence: 99%